Board monitoring of the chief financial officer: A review and research agenda. (9th February 2017) - Uhde, David Alexander; Klarner, Patricia; Tuschke, Anja
Abstract: Manuscript Type: Review Research Question/Issue: Research on how boards govern individual top management team (TMT) members, i.e., senior executives aside from the CEO, is still scarce and fragmented. In this study, we review extant research on board monitoring of the Chief Financial Officer (CFO) – an increasingly influential actor at the top of the firm – synthesize it, and propose an integrative future research agenda on board governing of the CFO. Research Findings/Insights: Our review of the accounting, finance, and management literatures reveals that extant research emphasizes the board's need to monitor the CFO as a major strategic actor in the firm. However, studies have frequently focused on selective aspects of board monitoring activities, neglecting how central board attributes influence effective governance of the CFO. We therefore develop a comprehensive model of board monitoring and advising of the CFO that addresses the role of board attributes in governance activities. Theoretical/Academic Implications: Our future research program on board governance of the CFO contributes to developing a better understanding of how board composition, structure, characteristics, and processes influence different board monitoring and advising activities. Practitioner/Policy Implications: We offer a framework for boards of directors responsible for governing CFOs, highlighting the factors they have to take into consideration when selecting, dismissing, and compensating the CFO and when ratifying her decisions and rendering advice on her proposals. We also provide CFOs with insights into the factors that influence their dismissal, compensation, and collaboration with the board.